Abnormal Presentation of Type III Oesphageal Atresia and TOF - Yaseen, Diaa Eldinn; Nugud, Faisal Abdel Galil; Elbashir, Mohamed Toum; Badrelmaarif, Mohammed Suror (مجلة الجزيرة للعلوم الصحية; مجلد 8 عدد 2 (2012), 2012)
_